Beyond the Internet of Things : everything interconnected - Batalla, Jordi Mongay; Mastorakis, George, 1978-; Mavromoustakis, Constandinos X., 1974-; Pallis, Evangelos, 1971- (Springer, 2017)
The major subjects of the book cover modeling, analysis and efficient management of information in Internet of Everything (IoE) applications and architectures. As the first book of its kind, it addresses the major new technological developments in the field and will reflect current research trends, as well as industry needs. It comprises of a good balance between theoretical and practical issues, covering case studies, experience and evaluation reports and best practices in utilizing IoE applications. It also provides technical/scientific information about various aspects of IoE technologies, ranging from basic concepts to research grade material, including future directions.
Keywords: Internet of things.; elektronické knihy; electronic books